Planning the evolution to broadband access networks: A multicriteria approach - Antunes, Carlos Henggeler (1998)
The interplay between continuing technical innovations, development of multifaceted modes of communication and market structure, among other factors, have raised new and complex problems concerning the strategic modernisation planning of telecommunications networks, namely regarding the evolution paths towards a wide range of new service offerings to be delivered to homes by using broadband technologies. However, decisions must be made by telecommunications operating companies or administrations in a turbulent environment, full of uncertainties with respect to reliable demand forecasts (for new services for which no past data is available), production costs and time to reach the market of some equipment based on brand new technologies, development of new services, etc. Moreover, strategic decisions to be made generally involve distinct, incommensurate and conflicting aspects; that is, problems are multicriteria in nature in the sense that economical, technological, market and social aspects are at stake. Therefore, in order to make well founded decisions, models should explicitly address those different objectives, so that decision makers and planning bodies may grasp the conflicting nature of the objectives and the trade-offs to be made in order to select satisfactory evolution plans. This paper presents a multicriteria model, which extends previous work by the authors, aimed at studying the evolution scenarios to deploy new supporting technologies in the access network to deliver broadband services to individuals and small enterprises.